2012
DOI: 10.1103/physrevb.85.245437
|View full text |Cite
|
Sign up to set email alerts
|

Isotope effect in the spin response of aluminum tris(8-hydroxyquinoline) based devices

Abstract: We studied the spin response of various magnetic field effects and magneto-transport in both protonated and deuterated aluminum tris(8-hydroxyquinoline) [Alq 3 ]-based organic light emitting diodes and spin-valve devices. Both conductivity-detected magnetic resonance in diodes and magneto-resistance in spin valves show substantial isotope dependence pointing to the importance of the hyperfine interaction (HFI) in the spin response of spin ½ charge polarons in Alq 3 . In addition the low field (B<20 mT) magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 26 publications
2
57
0
Order By: Relevance
“…In organics, the isotope effect is frequently studied by replacing H with D, i.e., deuteration. 7,9,10 In cases where H is the only HFI source, the effect of deuteration on the HFI is straightforward. For organics with other nuclear spins, the effect of deuteration on the HFI depends on how much the HFI originates from the H atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In organics, the isotope effect is frequently studied by replacing H with D, i.e., deuteration. 7,9,10 In cases where H is the only HFI source, the effect of deuteration on the HFI is straightforward. For organics with other nuclear spins, the effect of deuteration on the HFI depends on how much the HFI originates from the H atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Using layered devices based on Bphen/MTDATA -a well-known exciplex emitter -we show that the increase in EL emission intensity I due to small applied magnetic fields of order 100 mT is markedly larger at the high-energy blue end of the EL spectrum (∆I/I ∼11%) than at the low-energy red end (∼4%). Concurrently, the widths of the magneto-EL curves increase monotonically from blue to red, revealing an increasing hyperfine coupling between polarons and nuclei and directly providing insight into the energy-dependent spatial extent and localization of polarons.Several recent experiments have shown that small applied magnetic fields B on the order of 10-100 mT can induce substantial (∼10%) changes in the total light intensity emitted by organic light-emitting diodes (OLEDs) [1][2][3][4][5][6][7][8][9][10][11][12][13]. While initially surprising in view of the fact that the polymers and small molecules used in OLEDs are primarily composed of non-magnetic atoms (H, C, N), it was quickly appreciated that hyperfine spin interactions underpinned these phenomena.…”
mentioning
confidence: 99%
“…This precession leads to spin mixing between singlet and triplet polaron-pair states, which are precursors to exciton or exciplex formation in an OLED. Applied fields B suppress this hyperfineinduced mixing, altering the population balance between singlet and triplet excitons or exciplexes, which in turn modifies the electroluminescence (EL) efficiency.The detailed dependence of EL intensity on B allows direct insight into not only the rates of singlet and triplet exciton/exciplex formation, but also reveals the strength of hyperfine coupling and therefore provides a measure of the spatial extent (size) of the electron and hole polarons.In magneto-EL studies to date [1][2][3][4][5][6][7][8][9][10][11][12][13], only the total (spectrally-integrated) EL intensity was measured as a function of B. However, OLED emission spectra typically span a very broad wavelength range, reflecting the fact that excitons and exciplexes form over a wide range of energies, and with varying degrees of localization for which different hyperfine couplings may be expected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Compelling evidence exists that the HFI is important for spin mixing. Clear differences could be observed in studies of magnetic field effects in deuterated versus nondeuterated organic semiconductors [28,29]. Below we also discuss a recent report on direct electrical detection of nuclear spin manipulation in an OLED [30].…”
Section: Magnetic Field Effects In Organic Semiconductorsmentioning
confidence: 99%